Opendata dinamici per i servizi di infomobilità della Smartcity a Bari - Barbieri, Vincenzo; Coletta, Francesco (GEOmedia, 2015)
Il Comune di Bari ed AMTAB, hanno deciso di "liberare” a settembre 2014 i dati derivanti dal telecontrollo dei mezzi di trasporto AMTAB , rendendo li fruibili in modalità "opendata”. Questa iniziativa punta a soddisfare l'esigenza d'integrare le diverse soluzioni per la mobilità e realizzare un sistema di monitoraggio della mobilità sostenibile e intelligente nell'ambito del programma Bari Smart City. In September 2014 the City of Bari and AMTAB, the local public transport company, decided to open the data derived from the remote control of AMTAB buses with a creative commons CC0 license. The data published are both static and dynamic: they are accessible through web services and provide information, among others, on the list of bus stops and estimated times for the arrival of buses at the stops. These data are used to calculate information on the congestion level of traffic on the roads covered by the city buses. Such information are available as opendata too. This initiative is part of a Living Lab aiming to meet the need of the city of Bari for the integration of different mobility solutions and the implementation of an integrated system for the monitoring of the smart and sustainable mobility in Bari.